Efektivitas Penerapan Student Facilitator And Explaining Berbantuan Objek Langsung Pembelajaran IPA Siswa Sekolah Dasar - Fitri Rosalina Nurdin; Irmawanty; Amri Amal (CV Edujavare Publishing, 2024)
This research aims to find out what the science learning outcomes are before and after being taught using the Student Facilitator and Explaining learning model assisted by direct object media as well as the effectiveness of the Student Facilitator and Explaining learning model assisted by direct object media on science learning outcomes. The type of research used in this research is pre-experimental and is a quantitative type of research. The sample in this study was 17 students. Data collection techniques were carried out using learning results tests and observation sheets. Data analysis of research results was obtained from descriptive statistical data analysis and inferential data analysis. The research results show that the magnitude of science learning outcomes before being taught through the Student Facilitator and Explaining learning model assisted by direct object media is with an average score of 63 and a completion percentage of 43%. The magnitude of science learning outcomes after being taught through the Student Facilitator and Explaining learning model assisted by direct object media with an average score of 83 and a completion percentage of 100%. . Results of descriptive and inferential analysis testing with the help of SPSS 23.0 for Windows. the results of testing the research hypothesis using the right-hand collaborative t-test, obtained a t-value of 3.873. The ttable value of α = 0.05 and dk = 17 – 2 = 15 is 2.009, so the result obtained is tcount > ttable, namely 3.873 > 2.009. Based on these results, H0 is rejected. Thus, it can be stated that there was an increase in science learning outcomes for fifth grade students at SDN 57 Sangeran, Enrekang Regency before and after being taught using the Student Facilitator and Explaining learning model assisted by direct object media.